Delayed diagnosis of an intraorbital wooden foreign body. (2nd November 2018) - Bayramoğlu, Sadık Etka; Sayın, Nihat; Erdogan, Mehmet; Yıldız Ekinci, Dilbade; Uzunlulu, Nail; Bayramoglu, Zuhal
ABSTRACT: A 35-year-old male patient was presented with pain on his right upper eyelid. A piece of wood injured his orbital and supraorbital regions while working at a furniture factory 10 days prior to our hospital admission. It was learned that the patient was discharged following the primary would closure procedure. Subsequent to the craniofacial computed tomography, primary wound closure was performed in the emergency room of previous hospital. In our clinic, a skin suturing on the nasal side of the right eyebrow was inspected and a foreign body (FB) was palpated on the superonasal contiguity of the patients' right globe. A hyperdense FB measuring 30 × 10 × 5 mm in size with smooth margins on superonasal contour of the globe was detected. Superonasal orbitotomy was performed and the FB was completely removed. Finally, visual acuity was 20/20 and a mild residual ptosis was observed.